An economic optimization of evaporator and air collector area in a solar assisted heat pump drying system - Rahman, S. M. A.; Saidur , Rahman; Hawlader, Mohammad Nurul Alam (Pergamon, 2013)
This paper presents an economic optimization of evaporator and air collector area of a solar assisted heat pump drying system. Economic viability of solar heating systems is usually made by comparing the cost flows recurring throughout the lifetime of the solar and conventional alternative systems. Therefore, identification of optimum variables by using a simulation program and an economic analysis based on payback period of the system are presented in this paper. FORTRAN language is used to run the simulation. Effect of load and different economic variables on payback period is also investigated. Economic analysis reveals that system has sufficient amount of savings during the life cycle with a minimum payback period of about 4 years.